Phasic activation of ventral tegmental neurons increases response and pattern similarity in prefrontal cortex neurons - Motoko Iwashita (eLife, 2014)
Dopamine is critical for higher neural processes and modifying the activity of the prefrontal cortex (PFC). However, the mechanism of dopamine contribution to the modification of neural representation is unclear. Using in vivo two-photon population Ca2+ imaging in awake mice, this study investigated how neural representation of visual input to PFC neurons is regulated by dopamine. Phasic stimulation of dopaminergic neurons in the ventral tegmental area (VTA) evoked prolonged Ca2+ transients, lasting ∼30 s in layer 2/3 neurons of the PFC, which are regulated by a dopamine D1 receptor-dependent pathway. Furthermore, only a conditioning protocol with visual sensory input applied 0.5 s before the VTA dopaminergic input could evoke enhanced Ca2+ transients and increased pattern similarity (or establish a neural representation) of PFC neurons to the same sensory input. By increasing both the level of neuronal response and pattern similarity, dopaminergic input may establish robust and reliable cortical representation.